Post-marketing safety concerns with rimegepant based on a pharmacovigilance study - Jia-Ling Hu; Jing-Ying Wu; Shan Xu; Shi-Yan Qian; Cheng Jiang; Guo-Qing Zheng (The Journal of Headache and Pain, 2024)
Abstract Purpose This study aimed to comprehensively assess the safety of rimegepant administration in real-world clinical settings. Methods Data from the Food and Drug Administration Adverse Event Reporting System (FAERS) spanning the second quarter of 2020 through the first quarter of 2023 were retrospectively analyzed in this pharmacovigilance investigation. This study focuses on employing subgroup analysis to monitor rimegepant drug safety. Descriptive analysis was employed to examine clinical characteristics and concomitant medication of adverse event reports associated with rimegepant, including report season, reporter country, sex, age, weight, dose, and frequency, onset time, et al. Correlation analysis, including techniques such as violin plots, was utilized to explore relationships between clinical characteristics in greater detail. Additionally, four disproportionality analysis methods were applied to assess adverse event signals associated with rimegepant. Results A total of 5,416,969 adverse event reports extracted from the FAERS database, 10, 194 adverse events were identified as the “primary suspect” (PS) drug attributed to rimegepant. Rimegepant-associated adverse events involved 27 System Organ Classes (SOCs), and the significant SOC meeting all four detection criteria was “general disorders and administration site conditions” (SOC: 10018065). Additionally, new significant adverse events were discovered, including “vomiting projectile” (PT: 10047708), “eructation” (PT: 10015137), “motion sickness” (PT: 10027990), “feeling drunk” (PT: 10016330), “reaction to food additive” (PT: 10037977), etc. Descriptive analysis indicated that the majority of reporters were consumers (88.1%), with most reports involving female patients. Significant differences were observed between female and male patients across age categories, and the concomitant use of rimegepant with other medications was complex. Conclusion This study has preliminarily identified potential new adverse events associated with rimegepant, such as those involving the gastrointestinal system, nervous system, and immune system, which warrant further research to determine their exact mechanisms and risk factors. Additionally, significant differences in rimegepant-related adverse events were observed across different age groups and sexes, and the complexity of concomitant medication use should be given special attention in clinical practice.